Fiscal morality and the underground economy in countries of the European Union and the USA - Mititelu, Roxana Adriana; Amzuică, Bogdan Florian; Chiriac, Alina; Nișulescu, Ileana (Technium Social Sciences Journal, 2022)
The research was conducted to explore fiscal morality and underground economy of European countries and the US. The study was based on the assumption that the growth rate of an economy has a significant influence on tax compliance. In addition, the research investigated the effect of other factors on tax compliance of various countries. The factors included life expectancy, GDP growth rate, expenditure on education, and proportion of people living below the median income. Tax revenue was used to represent the level of tax compliance. The nations considered for this study included Germany, Italy, France, UK, and the US. Data was obtained from the World Bank Database, for the period 1971-2020. The findings depicted that economic growth was negatively associated with tax revenue. However, life expectancy, education expenditure, and poverty levels had a positive association with tax revenue. The regression models indicated that Italy had the most suitable model for estimation of tax compliance of fiscal morality among the selected countries.